The Impact of Covid-19 on Economic Growth - Suparmono Suparmono (Akademi Akuntansi YKPN Yogyakarta, 2021)
The Covid-19 pandemic in Indonesia since March 2020 has had an impact on negative economic growth for two quarters, namely minus 5.2 percent in the second quarter and minus 3.49 percent in the third quarter (yoy). Likewise, the economic growth of Kulon Progo Regency is expected to experience a drastic decline in 2021, after 2019/2019 had the highest growth reaching 18 percent.This article aims to analyze impact the Covid-19 pandemic has on the economy growth of Kulon Progo Regency per economic sector. This article also projections Kulon Progo's economic growth until 2024 using eleven projection methods. From the results of the projections carried out, the Gross Regional Domestic Product (GRDP) of Kulon Progo Regency in 2020 is predicted to slow down due to the Covid-19 pandemic case which affects almost all sectors. However, this decline only occurred in 2020, because in the following year several sectors are predicted to increase in line with the improving situation and operation of infrastructure projects. Several sectors that will increase, such as the transportation and warehousing sectors, due to normal activities at Yogyakarta International Airport (YIA). Based on the optimistic, moderate, and pessimistic scenario, Kulon Progo Regency's economic growth will continue to grow positively. There are two contributions of this research, firstly analyzing the impact of the pandemic and projecting the impact for the next 4 years and secondly, the projection is carried out using the best model of eleven methods.